Variability of Smoke Optical Properties in Eastern Mediterranean - Poutli, Maria; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Ene, Dragos; Michailidis, Konstantinos; Balis, Dimitrios; Hadjimitsis, Diofantos G. (My University, 2024)
Wildfires can be considered as a natural part of many ecosystems, but their frequency and heightened risk have been notably influenced by climate change. This amplified threat poses a significant concern that necessitates further study on the properties and behavior of smoke particles. The 2023 was a year of intense wildfires worldwide with Greece experiencing the largest wildfire in European history. A record-breaking forest fire activity was spotted in the Evros region, of northeastern Greece during August. The smoke plume reached different regions leading to an international concern. In this work, we focus on the study of optical properties related to the smoke particles observed in the atmosphere of Limassol, Cyprus, during the recent forest fires as retrieved by the PollyXT of the ERATOSTHENES CoE. In addition, measurements provided by the THELISYS lidar system in Thessaloniki are used synergistically to confirm the transport of smoke above the Limassol region.
Keywords: wildfires; remote sensing; optical properties; lidar